In the search of recovery: the 4ps for small and medium enterprises to recover after the pandemic - Irene Teresa Rebecca Hutabarat; Anita Maharani (Trigin Publisher, 2023)
This article describes a set of solutions that small and medium-sized businesses might utilize to recover economically after the epidemic. This paper was written using a variety of strategic management principles and marketing mix concepts from the literature. The research technique used in this study is a literature study methodology that collects secondary data from the search page, and also interviewed small and medium business owner. This research suggests that a variety of tactics that small and medium-sized businesses might adopt should be evaluated, particularly marketing mix strategies developed before the pandemic and their relevance after the government declared the epidemic over. The benefit in regards to this study was to present preparation of small and medium-sized business owners when facing challenges, especially the unpredicted ones